Rancang Bangun Aplikasi Poin Prestasi dan Poin Pelanggaran Siswa Berbasis Web Studi Kasus SMK PGRI 31 Jakarta Pusat - Yugi Setiawan; Fauziyah; Alexius Ulan Bani; Iskandar Zulkarnain (Jurnal Jaring SainTek, 2022)
SMK PGRI 31 JAKARTA is a vocational school located in Central Jakarta and has 3 majors, namely Marketing, Accounting and Office Administration. The information system for violation points and student achievements at SMK PGRI 31 Jakarta currently is in the process of recording violations still using handwritten cards, so the problem that occurs is that sometimes there is often loss of data that has not been recorded in the case book, as well as the slow process of point recapitulation. students thus hindering the action taken by the school. In defining needs and analyzing system development, it is done through data collection methods by means of observation, interviews with the counseling / BK section. The information system for points of violation and student achievement proposed in the process of awarding points made by the teacher has been systemized and immediately accepted by the guardians of the students, the proposal for making input points is expected to make it easier for counseling guidance teachers to make calls. The information system for violation points and student achievements uses the PHP and SQL Server programming languages ​​as databases. The information system for violation points and student achievement is expected to minimize the possibility of errors in making monthly reports